2017
DOI: 10.1007/s00198-017-3929-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between sarcopenia and functional outcomes among older patients with hip fracture undergoing in-hospital rehabilitation

Abstract: These findings support the systematic assessment of sarcopenia among older adults receiving rehabilitation programs to assist in the development of personalized treatment plans aimed at improving functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 35 publications
3
68
4
2
Order By: Relevance
“…In the present study, we considered the risk of a cumulative number of geriatric conditions as a proxy of vulnerability and showed its association with lower HGS in both female and male patients, and absolute and relative muscle mass at admission in male patients. A recent study in older inpatients showed that low muscle strength and muscle mass at admission leads to an increased risk of incomplete functional recovery during inhospital rehabilitation [25] , likely mediated by the increased vulnerability of these patients. Lower relative SMM at admission was only associated with being at risk of a higher cumulative number of geriatric conditions after adjusting for weight.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we considered the risk of a cumulative number of geriatric conditions as a proxy of vulnerability and showed its association with lower HGS in both female and male patients, and absolute and relative muscle mass at admission in male patients. A recent study in older inpatients showed that low muscle strength and muscle mass at admission leads to an increased risk of incomplete functional recovery during inhospital rehabilitation [25] , likely mediated by the increased vulnerability of these patients. Lower relative SMM at admission was only associated with being at risk of a higher cumulative number of geriatric conditions after adjusting for weight.…”
Section: Discussionmentioning
confidence: 99%
“…Our study applied both the ESPEN consensus and guidelines to describe the influence of basic and etiology-based diagnoses of malnutrition on clinical outcomes during hospitalization for postacute care. As malnutrition and disability are linked bidirectionally to mobility and disability (Landi et al, 2017), an early identification of malnourished patients would help the multidisciplinary care team to set realistic aims, plan therapeutic strategies, and provide the patient and caregivers with more precise information. The influence of the ESPEN consensus on clinical outcomes was recently reported in geriatric patients with diabetes in acute care (Sanz-París et al, 2016), but its influence on clinical and rehabilitation outcomes during hospitalization in postacute care has not previously been described…”
Section: Discussionmentioning
confidence: 99%
“…Women undergo an accelerated loss of muscle mass at an earlier age than men, beginning at the time of menopause [12] ; however, it appears men lose more muscle mass over the course of their lifetime compared to females [13] . Sarcopenia is defined by a decline in both quality and quantity of muscle [14] , and is a major contributor to decline in physical function and development of frailty with aging [15, 16] . Although there is no international consensus on the operational definition of sarcopenia [14] , a well-accepted definition based on muscle mass alone uses an appendicular skeletal mass index (ASMI) defined as either appendicular lean mass, measured by dual energy X-ray absorptiometry (DXA) [17] , or appendicular skeletal muscle mass measured by MRI (ASM) [18] , both adjusted for height [19, 20] .…”
Section: Sarcopeniamentioning
confidence: 99%